Molecular Mechanism of Action and Selectivity of Sodium Ch annel Blocker Insecticides - Silver, Kristopher; Dong, Ke; S. Zhorov, Boris (Current Medicinal Chemistry, 2017)
Sodium channel blocker insecticides (SCBIs) are a relatively new class of insecticides that are represented by two commercially registered compounds, indoxacarb and metaflumizone. SCBIs, like pyrethroids and DDT, target voltage-gated sodium channels (VGSCs) to intoxicate insects. In contrast to pyrethroids, however, SCBIs inhibit VGSCs at a distinct receptor site that overlaps those of therapeutic inhibitors of sodium channels, such as local anesthetics, anticonvulsants and antiarrhythmics. This review will recount the development of the SCBI insecticide class from its roots as chitin synthesis inhibitors, discuss the symptoms of poisoning and evidence supporting inhibition of VGSCs as their mechanism of action, describe the current model for SCBI-induced inhibition of VGSCs, present a model for the receptor for SCBIs on VGSCs, and highlight differences between data collected from mammalian and insect experimental models.
Keywords: insecticide receptors